2021
DOI: 10.5194/se-12-2087-2021
|View full text |Cite
|
Sign up to set email alerts
|

Coupled dynamics and evolution of primordial and recycled heterogeneity in Earth's lower mantle

Abstract: Abstract. The nature of compositional heterogeneity in Earth's lower mantle remains a long-standing puzzle that can inform about the long-term thermochemical evolution and dynamics of our planet. Here, we use global-scale 2D models of thermochemical mantle convection to investigate the coupled evolution and mixing of (intrinsically dense) recycled and (intrinsically strong) primordial heterogeneity in the mantle. We explore the effects of ancient compositional layering of the mantle, as motivated by magma ocea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 125 publications
2
25
0
Order By: Relevance
“…Later-stage partial melting induced by hot anomalies in a largely solidified mantle leads to small-scale heterogeneity as different rock components melt under different conditions and have different affinity to partition into the molten phase (e.g., Hofmann 1997). Such processes compete with mantle convective stirring that tends to homogenise lateral variation, but the mixing time scales in the mantle are large and compositional heterogeneity occurs likely across multiple scales in the Earth's present mantle (e.g., Tkalčić et al 2015), as is also supported by modelling studies (Gülcher et al 2021). However, terrestrial plate tectonics continuously induces new heterogeneity by deep crustal subduction, which may be less relevant to Venus without plate tectonics.…”
Section: Mineralogy and Compositional Variationmentioning
confidence: 93%
“…Later-stage partial melting induced by hot anomalies in a largely solidified mantle leads to small-scale heterogeneity as different rock components melt under different conditions and have different affinity to partition into the molten phase (e.g., Hofmann 1997). Such processes compete with mantle convective stirring that tends to homogenise lateral variation, but the mixing time scales in the mantle are large and compositional heterogeneity occurs likely across multiple scales in the Earth's present mantle (e.g., Tkalčić et al 2015), as is also supported by modelling studies (Gülcher et al 2021). However, terrestrial plate tectonics continuously induces new heterogeneity by deep crustal subduction, which may be less relevant to Venus without plate tectonics.…”
Section: Mineralogy and Compositional Variationmentioning
confidence: 93%
“…While we have not included the effects of a dense, primordial layer in our simulations, we do not refute the potential for such compositions to exist in the mantle and play a role in LLSVP formation. Studies which combine both primordial and recycled OC material (Ballmer et al., 2016; Gülcher et al., 2021; Jones et al., 2021) will also benefit from including the effects of radiogenic heating in each of the compositions (Citron et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The first is that LLSVPs are composed of dense primordial material (Deschamps et al., 2011; Garnero & McNamara, 2008; Labrosse et al., 2007; M. Li & McNamara, 2018) and the second is that they formed from the accumulation of recycled oceanic crust (henceforth referred to as OC) (Christensen & Hofmann, 1994; Coltice & Ricard, 1999; Tackley, 2011). A third scenario arises from this, where LLSVPs may comprise heterogeneity from both recycled OC and primordial material, a so‐called basal melange (Gülcher et al., 2021; Jones et al., 2021; Tackley, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Giuliani et al ( 2021 ) noted that the PREMA component found in most kimberlite sources may be contained within LLSVPs. However, the distribution of PREMA in the mantle remains uncertain; for example, "blobs/streaks" of ancient material are also modeled to exist and persist throughout the ambient mantle ( Ballmer et al, 2017;Becker et al, 1999;Brandenburg et al, 2008;Gülcher et al, 2021;Jones et al, 2021 ).…”
Section: Mantle Plume-driven Geochemical Enrichment Of the Kaavi-kuop...mentioning
confidence: 99%